2018
DOI: 10.1021/acs.jmedchem.7b01634
|View full text |Cite
|
Sign up to set email alerts
|

Design and Syntheses of Highly Potent Teixobactin Analogues against Staphylococcus aureus, Methicillin-Resistant Staphylococcus aureus (MRSA), and Vancomycin-Resistant Enterococci (VRE) in Vitro and in Vivo

Abstract: The cyclic depsipeptide, teixobactin, kills a number of Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), and Mycobacterium tuberculosis without detectable resistance. To date, teixobactin is the only molecule in its class that has shown in vivo antibacterial efficacy. In this work, we designed and synthesized 10 new in vivo ready teixobactin analogues. These analogues showed highly potent antibacterial activities against Staphylococcus aureus, MRSA, and vancomycin-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 19 publications
(82 reference statements)
4
81
0
3
Order By: Relevance
“…aureus) isolates. It was found that the minimum inhibitory concentrations (MICs) were comparable with those from previous reports (Table ) including matching MIC values for S . aureus ATCC29213 (0.5 μg/mL) …”
Section: Resultssupporting
confidence: 82%
“…aureus) isolates. It was found that the minimum inhibitory concentrations (MICs) were comparable with those from previous reports (Table ) including matching MIC values for S . aureus ATCC29213 (0.5 μg/mL) …”
Section: Resultssupporting
confidence: 82%
“…Introduction of another d -Arg4 substitution of d -Gln4 in the context of Leu10 substitution of allo -End10, however, further reduces the minimal inhibitory concentrations of the Txb analog 24. Therefore, we speculate that the role of this d -Arg4 residue is also as a positively charged secondary phosphate-coordinator, presumably one that binds the phosphate group farther away from the cyclodepsipeptide ring.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, recent discoveries of several highly active Txb analogs2224 all contain allo -End10 substitutions with medium-sized hydrophobic residues, suggesting that this secondary phosphate coordinating group at the residue 10 position is not absolutely required. Introduction of another d -Arg4 substitution of d -Gln4 in the context of Leu10 substitution of allo -End10, however, further reduces the minimal inhibitory concentrations of the Txb analog 24.…”
Section: Discussionmentioning
confidence: 99%
“…[145] Thel ack of resistance development so far is ar esult of the multifacetted MoA, combined with the fact that teixobactin addresses ah ighlyconserved non-protein target. [152] In-depth structureactivity relationship (SAR) studies,e specially aiming to replace the synthetically inconvenient l-allo-enduracididine (l-allo-End) amino acid, led to the identification of various potent derivatives,i ncluding d-Arg 4 -Leu 10 -teixobaction ( Figure 6).…”
Section: Reviewsmentioning
confidence: 99%